PERAN MUTASI DALAM PENGEMBANGAN KARIR PEGAWAI PADA KANTOR CAMAT LOLOFITU MOI KABUPATEN NIAS BARAT - Zai, Junlifes; Abadi Mendrofa, Syah; Mendrofa, Yupiter; Halawa, Odaligoziduhu (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
This research aims to find out how the implementation and impact of mutations at the Lolofitu Moisub-district office, employee career development and factors inhibiting employee career developmentat the Lolofitu Moi sub-district office. It was found that several employees had held the same positionfor a long time without any transfer or promotion in recent years. This could lead to boredom becausethey were stuck in the same routine and did not experience adequate career development. This research uses qualitative research methods, conducting in-depth interviews with employees at the Lolofitu Moi District Office. The results of the research show that the implementation of transfers at the Lolfitu Moi sub-district office is still not effective, where there are still several employees who have not been transferred in the last few years. The implementation of the transfer has had a positive impact on employees at the Lolofitu Moi sub-district office. Employee career development at the Lolfitu Moi sub-district office involves strategies, namely performance evaluation, training, transfers and promotions. However, there are several obstacles, namely limitations in training and promotion opportunities which depend on agency policies and quotas.